Pengaruh kurs dan harga ekspor terhadap daya saing ekspor komoditas unggulan Provinsi Jambi - Muslimin Andika Putra; Emilia Emilia; Candra Mustika (e-Journal Perdagangan Industri dan Moneter, 2018)
The purpose of this research are: 1) to analyze competitiveness of commodity of areca nut, vegetable oil, rubber and paper of Jambi Province; 2) to analyze the influence of exchange rate and export price to export competitiveness of rubber, areca nut, vegetable oil and paper of Jambi Province. The data used are secondary data from 2000 - 2015, including: 1) Rupiah exchange rate against US Dollar; 2) Export price of rubber commodity, areca nut, vegetable oil and paper of Jambi Province; 3) Export value of rubber commodity, areca nut, paper, vegetable oil of Jambi Province and Indonesia. The analysis tools used are: a) Revealed Comparative Advantage (RCA); b) Multiple Linear Regression Analysis. The results of the study found that: 1) rubber commodities and areca nut commodities in Jambi Province were competitive while paper and vegetable oil commodities were not competitive; 2) exchange rate, export price has significant effect on export competitiveness of rubber, areca nut, paper and vegetable oil in Jambi Province Keywords: Competitiveness, Exchange Rate, Export Price. Abstrak Tujuan dari penelitian ini untuk menganalisis daya saing dari komoditi pinang, minyak nabati, karet dan kertas Provinsi Jambi dan juga untuk menganalisis pengaruh Kurs dan harga ekspor terhadap daya saing ekspor komoditi karet, pinang, minyak nabati dan kertas Provinsi Jambi. Data yang digunakan adalah data sekunder dari tahun 2000 – 2015, mencakup: 1) Kurs rupiah terhadap Dolar Amerika; 2) Harga ekspor komoditi karet, pinang, minyak nabati dan kertas Provinsi Jambi; 3) Nilai ekspor komoditi karet, pinang, kertas, minyak nabati Provinsi Jambi dan Indonesia. Alat analisis yang digunakan adalah: a) Revealed Comparative Advantage (RCA); b) Analisis Regresi Linear Berganda. Hasil penelitian menemukan bahwa: 1) komoditas karet dan pinang Provinsi Jambi berdaya saing sedangkan komoditas kertas dan minyak nabati tidak berdaya saing; 2) kurs, harga ekspor berpengaruh signifikan terhadap daya saing ekspor karet, pinang, kertas dan minyak nabati di Provinsi Jambi Kata Kunci : Daya Saing, Kurs, Harga Ekspor.